Special Issue “Halophilic Microorganisms” - Cristina Sánchez-Porro (Microorganisms, 2023)
Hypersaline environments are mainly represented by aquatic systems, such as solar salt ponds or natural salt lakes, as well as by the sediments of these hypersaline aquatic ecosystems and soils with high salt content [...]